2009
DOI: 10.1590/s0100-54052009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de lodo de esgoto sobre patógenos habitantes do solo e severidade de oídio da soja

Abstract: Sewage sludge, complying with environmental demands, has potential for use in agriculture. The incorporation of sewage sludge may changes the chemical, physical and biological soil properties, for being rich in macro and micronutrients and organic matter. These changes can provide benefits such as the increase in the availability of nutrients for plants, and the induction of suppressiveness to soilborne plant pathogens and resistance to foliar diseases. However, it may influence negatively the biological and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In such study, there were no treatment effects on the suppressiveness of R. solani and M. phaseolina [14]. Those authors, in the same soils, evaluated the effect of sewage sludge on the severity soybean powdery mildew (Erysiphe diffusa), and observed that the disease severity was reduced with of increase in the concentration of sludge in the soil.…”
Section: Applied and Environmental Soil Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…In such study, there were no treatment effects on the suppressiveness of R. solani and M. phaseolina [14]. Those authors, in the same soils, evaluated the effect of sewage sludge on the severity soybean powdery mildew (Erysiphe diffusa), and observed that the disease severity was reduced with of increase in the concentration of sludge in the soil.…”
Section: Applied and Environmental Soil Sciencementioning
confidence: 99%
“…lycopersici in tomato plants. Araújo and Bettiol [14] conducted two experiments to evaluate the effects of sewage sludge on seedling emergence, damping-off incidence, and severity of R. solani and Macrophomina phaseolina in soybean using soil samples collected in the Jaguariúna experiment [32] after four (1999 to 2001) successive applications of sewage sludge (Tables 1 and 2). In this case, the experiments were conducted in pots and the soil was artificially infested with the pathogens.…”
Section: Effect Of Sewage Sludge Onmentioning
confidence: 99%
See 1 more Smart Citation
“…(FMO)....................................................................................................................................39 FMO).........................................................................................40 Desdobramento da interação entre os níveis de fertilizante organomineral e a fonte de matéria orgânica em relação à altura de plantas (cm) aos 90 DAS para o lodo de esgoto (APLE) e torta de filtro (APTF) em sorgo………………………………………......42Tabela 12 -Desdobramento da interação entre os níveis de fertilizante organomineral e fonte de matéria orgânica em relação à altura total de plantas (cm) para o lodo de esgoto (ATPLE) e torta de filtro (ATPTF) em sorgo……………………………………...……..................…43 INTRODUÇÃO ................................................................................................................................ 2 OBJETIVOS ..................................................................................................................................... Objetivo Geral ........................................................................................................................... ........................................................................................................ ...................................................................... Legislação brasileira ................................................................................................................. Classificação dos fertilizantes ............................................................................................ ............................................................. .................... ........................................................................................................................... ...........................................................................................................................MÉTODOS ............................................................................................................. ..................................................................................................... 6 CONCLUSÃO .................................................................................................................................. 7 CONSIDERAÇÕES FINAIS .......................................................................................................... REFERÊNCIAS BIBLIOGRÁFICAS .............................................................................................. ................................... ....................................................... ANEXO I .............................................................................................................................................. Isso trouxe um insumo agrícola inovador para a produção de fertilizantes organominerais, que permitem uma maior utilização de nutrientes disponíveis do que os fertilizantes convencionais.Outros benefícios potenciais da matéria orgânica adicionada ao fertilizante é o controle de fitopatógenos do solo.Tomazeli et al (2011) observaram que o incremento da atividade microbiana de agentes decompositores, promove uma redução do número das estruturas de sobrevivência dos patógenos e isto minimiza os sintomas de doenças em plantas causadas pelo fungo Sclerotium rolfsii. Estudos demonstraram que o lodo de esgoto aplicado ao solo melhorou a emergência de plântulas e diminuiu a severidade da Erysiphe diffusa(ARAÚJO & BETTIOL, 2009). não produção de rejeitos, mas sim, de novos insumos como uma ferramenta da logística de fluxos de retorno, oriundos de seu ciclo ou de outros ciclos produtivos(MARCHI, 2011).Essa evolução no setor de fertilizantes com base na logística reversa tornou as empresas mais competitivas, com o uso estratégico de seus produtos pós-consumo, retorno financeiro e adequada gestão ambiental(TELES et al, 2016).Também, o uso de ...…”
unclassified